Photobiological Implications of Folate Depletion and Repletion in Cultured Human Keratinocytes - Williams, Joshua D. (2010)
Folate nutrition is critical in humans and a high dietary folate intake is associated with a diminished risk of many types of cancer. Both synthetic folic acid and the most biologically abundant extracellular reduced folate, 5-methyltetrahydrofolate, are degraded under conditions of ultraviolet radiation (UVR) exposure. Skin is a proliferative tissue with increased folate nutrient demands due to a dependence upon continuous epidermal cell proliferation and differentiation to maintain homeostasis. Regions of skin are also chronically exposed to UVR, which penetrates to the actively dividing basal layer of the epidermis, increasing the folate nutrient demands in order to replace folate species degraded by UVR exposure and to supply the folate cofactors required for repair of photo-damaged DNA. Localized folate deficiencies of skin are a likely consequence of UVR exposure. We report here a cultured keratinocyte model of folate deficiency that has been applied to examine possible effects of folate nutritional deficiencies in skin. Utilizing this model, we were able to quantify the concentrations of key intracellular folate species during folate depletion and repletion. We investigated the hypotheses that the genomic instability observed under conditions of folate deficiency in other cell types extends to skin, adversely effecting cellular capacity to handle UVR insult and that optimizing folate levels in skin is beneficial in preventing or repairing the pro-carcinogenic effects of UVR exposure. Folate restriction leads to rapid depletion of intracellular reduced folates resulting in S-phase growth arrest, increased levels of inherent DNA damage, and increased uracil misincorporation into DNA, without a significant losses in overall cellular viability. Folate depleted keratinocytes were sensitized toward UVR induced apoptosis and displayed a diminished capacity to remove DNA breaks resulting from both photo and oxidative DNA damage. Thus, folate deficiency creates a permissive environment for genomic instability, an early event in the process of skin carcinogenesis. The effects of folate restriction, even in severely depleted, growth-arrested keratinocytes, were reversible by repletion with folic acid. Overall, these results indicate that skin health can be positively influenced by optimal folate nutriture.